Academic Teams and Commercialization in the Life Sciences - Clayton, Paige; Feldman, Maryann (Frontiers in Research Metrics and Analytics, 2021)
We review the literature on entrepreneurial team formation with a focus on data to study academic teams and summarize our empirical work on the life sciences industry. We consider how academics form teams to start new companies and the implications of various configurations on firm behavior with regards to patenting, survival and firm growth. We present several empirical challenges facing research on academic teams and conclude with suggestions for future research.